The Journey to School as an Influencing Factor on School Grades at Vocational Colleges - Paape, Björn; Maus, Christoph; Kiereta, Iwona; Demir, Yasemin; Demming, Jonas; Homfeld, Antonia; Klubert, Philipp; Korac, Erin; Kutlu, Ronai; Lachmann, Sebastian; Schreiber, Diana; Skrijeli, Amir; et al. (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
This study aims to investigate the relationship between travelling to school and the academic performance of vocational school students. In doing so, the study draws on teaching-learning theories as well as previous studies on travel to school factors. The results of the study show that an active journey to school can improve well-being, which in turn has a positive effect on grades. However, the data did not confirm that an active journey to school leads directly to better grades or that longer journeys to school have a negative impact on grades. These results emphasise the role of the journey to school for the well-being of pupils. It can therefore be assumed that travelling to school as part of students' daily lives plays an important role in their emotional well-being and should therefore be considered in a broader context when it comes to creating a conducive educational environment.